Forecast accuracy test of stochastic volatility models: traditional models vs Volatility Hang Seng Index - Pan, Fangxin (2013)
There are many researchers doing the work of evaluating the forecast performance between ARCH or GARCH type of volatility models and implied volatility index (mostly VIX). Since people have realised the importance of VIX now, the study about the forecast ability of implied volatility index model is emphasized. In this paper, the author has compared eight different models including the ARCH and GARCH model with the implied volatility index Volatility index of Hang Seng index which is seldom studied in literature. The importance and development of volatility index has been discussed. The difference between VIX and Hang Seng Volatility index has also been discussed in details. A history of similar empirical work has been displayed. The work has also provided the detailed methodology that has been used in this paper.